Effect of argon-ion irradiation on cavity formation and evolution in 18Cr10NiTi austenitic steel - Tolstolutskaya, G.D.; Karpov, S.A.; Kalchenko, A.S.; Kopanets, I.E.; Nikitin, A.V.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2020)
The swelling behavior of 18Cr10NiTi austenitic stainless steel irradiated with energetic Ar-ions in the dose range of 40…105 displacements per atom (dpa) with simultaneously implanted argon to the levels of 0.08…6.3 at.% at temperatures of 550…700 °C was investigated. Transmission electron microscopy (TEM) has been used to study the microstructure evolution and to determine the dependence of swelling on the damage and Ar concentration. It is shown that the highest density and average size of the cavities was observed in the region of the calculated peak damage and Ar concentration. Argon was found to promote cavity swelling at lower temperature. At simultaneous creation of defects and argon implantation it was found a shift of swelling curve to higher temperatures compared to metallic-ion irradiation. The cavity swelling behavior of an austenitic 18Cr10NiTi steel irradiated with energetic argon ions are compared with those resulting from helium implantation.